1998
DOI: 10.1006/cbir.1998.0263
|View full text |Cite
|
Sign up to set email alerts
|

Propionic Acid Stimulates Superoxide Generation in Human Neutrophils

Abstract: Short-chain carboxylic acids are the metabolic by-products of pathogenic anaerobic bacteria and are found at sites of infection in millimolar quantities. We previously reported that propionic acid, one of the short-chain carboxylic acids, induces an increase in intracellular Ca2+ ([Ca2+]i) in human neutrophils. Here we investigate the effect of propionic acid on superoxide generation in human neutrophils. Propionic acid (10 mm) induced inositol 1,4, 5-trisphosphate (IP3) formation and a rapidly transient incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…The effect of propionate or butyrate on reactive oxygen species synthesis by neutrophils, on the other hand, remains controversial. Some authors have reported increased reactive oxygen species production by SCFAs [124,125], while others have demonstrated inhibitory effects [126,127]. Controversy also surrounds the possible impact of SCFAs on microglial production of reactive oxygen species, NO, prostaglandin-E2, etc.…”
Section: Effects Of Scfas On Cytokine Production By Antigen-presentinmentioning
confidence: 99%
“…The effect of propionate or butyrate on reactive oxygen species synthesis by neutrophils, on the other hand, remains controversial. Some authors have reported increased reactive oxygen species production by SCFAs [124,125], while others have demonstrated inhibitory effects [126,127]. Controversy also surrounds the possible impact of SCFAs on microglial production of reactive oxygen species, NO, prostaglandin-E2, etc.…”
Section: Effects Of Scfas On Cytokine Production By Antigen-presentinmentioning
confidence: 99%
“…They also play a role in cell signalling [91] and neurotransmitter synthesis and release [92]. Moreover, SCFA have been shown to increase the synthesis of dopamine and its related catecholamines through induction of tyrosine hydroxylase, a key enzyme in the synthesis of catecholamines [93].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…Acetate, propionate and butyrate represent the most often described SCFAs that are capable of immune activation. SCFAs affect neutrophil function and migration [12][13][14][15] , and inhibit tumor necrosis factor-α (TNF-α) or interleukin-1ÎČ (IL-1ÎČ)-induced vascular cell adhesion molecule-1 (and intercellular adhesion molecule-1) surface expression [16] . In addition, SCFAs reduce adherence of monocytes or lymphocytes to cytokinestimulated human umbilical vein endothelial cells [17] , and inhibit interferon-Îł (IFN-Îł) signaling [18,19] , a possible regulator of inflammation in inflammatory bowel disease (IBD).…”
Section: Introductionmentioning
confidence: 99%